1996
DOI: 10.1046/j.1365-2265.1996.8290840.x
|View full text |Cite
|
Sign up to set email alerts
|

The 24‐hour rhythm of oxytocin and Β‐endorphin secretion in human pregnancy

Abstract: Reciprocal 24-hour rhythms were demonstrated between oxytocin and beta-endorphin; however, it is not clear whether this relationship is causal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 10 publications
0
33
1
1
Order By: Relevance
“…In contrast to Bakker et al, in primipare late term women, we have found that labor duration and active phase length of labor is shorter in the evening group than in the morning group. Our results can be explained by circadian rhythm of oxytocin concentration that was documanted by human and animal studies [10][11][12][13][14][15]. Oxytocin concentrations and myometrial oxytocin receptors increase during evening and night time with a decreased estradiol/progesterone ratio.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to Bakker et al, in primipare late term women, we have found that labor duration and active phase length of labor is shorter in the evening group than in the morning group. Our results can be explained by circadian rhythm of oxytocin concentration that was documanted by human and animal studies [10][11][12][13][14][15]. Oxytocin concentrations and myometrial oxytocin receptors increase during evening and night time with a decreased estradiol/progesterone ratio.…”
Section: Discussionmentioning
confidence: 94%
“…This finding may relate to the possible influence of endogenous analgesic agents, which have a diurnal acrophase, which is particularly evident in β-endorphin, adrenocorticotropic hormone and cortisol (Allolio et al, 1990;Lindow et al, 1996). Furthermore, it is also plausible that this nocturnal acrophase of labour pain may be related to the inhibition of melatonin secretion following the sleep deprivation commonly associated with artificial light stimulation (photo-inhibition) (LeGates et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Neurohumoral changes justify the lower intensity of matutinal and evening pain, since there is an abundance of central anti-nociceptive neurotransmitters: endorphins, enkephalins, and noradrenaline, during the day (light phase). Besides the nocturnal increase in melatonin, serotonin, and acetylcholine (anti-nociceptive), a drastic reduction in the levels of endorphins, corticosteroids, as well as the elevation of pro-nociceptive mediators (histamine, PG, oxytocin, cytokines) are also seen [47][48][49] .…”
Section: Chronobiology Of Dystocia -Circadian Variation 1) Painmentioning
confidence: 99%
“…However, pain perception is subjective, individual, and non-transferable. Unlike the matutinal and afternoon periods, labor pain is more severe at night due to neurohumoral changes, nocturnal acrophase of pro-nociceptive mediators (histamine, prostaglandins, oxytocin) associated with exhaustion or sleep deprivation of the parturient 7,8,12,13,47 . In the evolutionary point of view, a lower pain threshold at night has contributed for labor acceleration: faster delivery is aimed at protecting the newborn of the Homo sapiens against natural predators since his nomadic dislocation from central Africa thousands of years ago.…”
Section: Chronobiology Of Dystocia -Circadian Variation 1) Painmentioning
confidence: 99%
See 1 more Smart Citation